PENGARUH RASIO PROFITABILITAS DAN EVA TERHADAP HARGA SAHAM PADA SEKTOR INDUSTRI MANUFAKTUR DI BEI TAHUN 2007-2010 - Haryuningputri, Meilinda; Tri Widyarti, Endang (Faculty of Economics and Business Diponegoro University, 2012)
Capital market are such medium whereas long term valuable letters being sale and bought. Within capital market, company get relative cheap fund, because company didn’t need to paid capital cost or capital cost could be pressed. Valuable letter which often trade in capital market was share. Share was valuable letter as participation evidence or both individual and institution ownership. Much factors which could influence share price such ROA, ROE, ROS, EPS and EVA. Aim of this research was to analyzed influence of ROA, ROE, ROS, EPS and EVA to share price, both partially or simultaneously. Population and sample within this research were all of manufacture productions which registered within BEI from 2007 – 2010. Sampling collection technique was purposive sampling and obtained sample about 112 companies. Data type was secondary. Data collection sample used documentation. Analysis technique used was double regression.